The Effect of Premium Income, Investment Returns, Claim Expenses, and Operating of Net Profit on Sharia Life Insurance Company - Hissiyah, Calista Noorma; Meylianingrum, Kurniawati (UNISSULA, 2023)
Risk is a potential loss that a company cannot predict. However, risks can be mitigated by dividing or enduring each other. This research wants to re-examine the research gap with the same theme. This research uses quantitative methods with a descriptive approach. The results showed that premium income and investment returns partially affected net profit. In contrast, claim expenses and operating expenses did not have a significant effect on net profit. Then simultaneous test results show that Premium Income, Investment Returns, Claim Expenses, and Operating Expenses to Net Profit together or simultaneously have a significant effect on net profit in Sharia life insurance.